تقييم بعض الصفات الإنتاجية و المورفولوجية لسلالات من الذرة الصفراء تحت ظروف العدوى الطبيعية بحفار ساق الذرة الكبير Sesamia cretica - حربا نزار; السمارة موسى; معلا نزار; اسعد نادين (Latakia University Journal -Biological Sciences Series, 2013)
أجري هذا البحث في حقول محطة بحوث سيانو التابعة للهيئة العامة للبحوث العلمية الزراعية في اللاذقية, حيث تم تقييم حساسية ست سلالات من الذرة الصفراء وفق تصميم القطاعات العشوائية الكاملة للموسم 2012وهي IL.257-09 P1, IL.298-09(P2 ), IL.286-09 (P3), IL.255-09 (P4), (P5) IL.262-09, IL.228-09 (P6) للإصابة بحفار ساق الذرة الكبير Sesamia cretica Led.تحت الظروف الطبيعية ومقارنتها مع الشاهد (غوطة 82) كونه الصنف الأكثر زراعة في سورية. سجلت أعلى نسبة للإصابة وموت القمة النامية على السلالة (P4) بعد (3) أسابيع من الإنبات حيث وصلت إلى %13.97و 7.5 % على التوالي, وهي السلالة المفضلة لوضع البيض, بينما كانت أقل نسبة إصابة على السلالة (P2) حيث كانت %2.8 و2.17% لموت القمة النامية. أما عند الحصاد فكانت أعلى نسبة للإصابة على السلالةP4 (43 %) وأقلها على السلالة P2 وهي (15.1) %, سجلت أكثر عدد ثقوب في النبات و أعلى عدد أنفاق و أطول منطقة محفورة على السلالة السورية (P4) حيث وصلت 3.25/نبات و 2.4/نبات و %12.05 على التوالي, بينما كان أقل عدد ثقوب وأقل عدد من الأنفاق وأقل مسافة محفورة على السلالة (P2)وبلغت 1.64/نبات , 0.5/نبات , 3.12% على التوالي. لم تكن هناك فروق معنوية بين السلالات المختلفة في أعداد اليرقات في النبات حيث تراوحت أعدادها بين 0.2-0.8 /نبات, في حين وجدت فروق معنوية بينها من حيث النسبة المئوية للفقد في عدد حبوب المحصول وقد تراوحت بين 14.2-18.3 %, وكذلك بالنسبة للفقد في وزن 100 حبة حيث تراوحت بين 5.9-7.5 %, سجلت السلالتين (P4), (P5) أعلى نسبة للفقد في الغلة وبلغت (23.76 –% ( 23.81 على التوالي, في حين سجلت السلالة P2 أقل نسبة للفقد % 18.7. وكما وجدت فروق معنوية بين السلالات المدروسة من حيث الصفات التالية: الإزهار المؤنث, ارتفاع النبات, ارتفاع العرنوس, النضج الفسيولوجي, طول العرنوس, قطر العرنوس, عدد الصفوف بالعرنوس, عدد الحبوب بالصف, وزن 100 حبة, وكان أفضلها السلالات P1, P2, P6للاستخدام في برامج التربية اللاحقة لمقاومة حشرة حفار ساق الذرة الكبير Sesamia cretica. This study was conducted at the field of the research station Sianow of General Commission for Scientific Agricultural Research at Lattakia, to evaluate the susceptibility of 6 strains of maize ( IL.257-09)P1), IL.298-09)P2 ( , IL.286-09) P3( , IL.255-09 )P4), IL.262-09 (P5), IL.228-09) P6 (), against the natural infestation by large corn stem borer , Sesamia cretica Led. They were Compared with control (Ghouta 82).because it is the most growing variety in Syria, in the season 2012, the experiment was designed at randomized complete blocks (R.C.B.D), The highest infection rate and dead hearts were recorded on strain (P4), after (3) weeks of germination and which reached to 13.97%, 7.5% respectively, and distinguished of being preferable strain for oviposition, whereas the least infection was on the strain (P2) 2.8%, 2.17% of dead hearts. At harvest the highest infection rate was at P4 (43%), and the lowest was at (P2) (15.1%). Syrian strain (P4) recorded the most number of holes/plant, highest number of tunnels and the longest area of stem tunneled/plant (3.25 / plant, 2.4 / plant, 12.05%) respectively. whereas the strain (P2) recorded less number of holes/plant, the lowest number of tunnels and less distance of stem tunneled/plant (1.64 / plant, 0.5 / plant, 3.12%) respectively. There were no significant differences between the different strains in the number of larvaes in the plant where the numbers ranged from 0.2-0.8 / plant, whereas there were significant differences between them, as percentage of loss in the number of grains, it has ranged between 2.14 - 3.18%, the percentage of loss of weight of 100 tablets was between 5.7 - 9.5 %. Strains (P4) and (P5) recorded the highest percentage of loss of yield and reached (23.76-23.81) %, respectively. Whereas P2 recorded the lowest percentage of loss with 18.7%. There were significant differences between the studied strains of the following qualities: Days to silking, Plant height:, Ear height, physiological maturity, Ear length, diameter Ear, Number of rows per Ear, Number of kernels per row, 100-Kernel weight, the best strains were P1, P2, P6 for using at subsequent breeding programs for resistance of large corn stem borer insect, Sesamia cretica.